Senescence: General aspects about morphophysiology in the process of oral aging (Research, Society and Development, 2021)
Objective: This study aimed to perform an expository review about the aging process of oral tissues, correlating the information available in the literature to a conceptual and terminological view. For this purpose, a search was performed in the literature with reference to SCIELO, MEDLINE and Health Portals databases. Methods: The methodology used was the bibliographic, an explanatory research, combined with a contextualization of the data, where the main intention was to make science in the scope of qualitative methods and techniques of research. Where the inclusion criteria were availability of the full text of the study, to demonstrate clarity in the methodological detail used and to be available in Portuguese or English. Conclusion: Through the perquirition performed in this study, it was possible to discuss in an enriching way the proposed theme, encompassing several physiological aspects, morphological and external characteristic, while main actors in the process of Oral senescence.